Polyclonal Regulatory T Cell Manufacturing Under cGMP: A Decade of Experience - Balcerek, Joanna; Shy, Brian R.; Putnam, Amy L.; Masiello, Lisa M.; Lares, Angela; Dekovic, Florinna; Acevedo, Luis; Lee, Michael R.; Nguyen, Vinh; Liu, Weihong; Paruthiyil, Sreenivasan; Xu, Jingying; et al. (Frontiers in Immunology, 2021)
We report on manufacturing outcomes for 41 autologous polyclonal regulatory T cell (PolyTreg) products for 7 different Phase 1 clinical trials over a 10- year period (2011-2020). Data on patient characteristics, manufacturing parameters, and manufacturing outcomes were collected from manufacturing batch records and entered into a secure database. Overall, 88% (36/41) of PolyTreg products met release criteria and 83% (34/41) of products were successfully infused into patients. Of the 7 not infused, 5 failed release criteria, and 2 were not infused because the patient became ineligible due to a change in clinical status. The median fold expansion over the 14-day manufacturing process was 434.8 -fold (range 29.8-2,232), resulting in a median post-expansion cell count of 1,841 x 106 (range 56.9-16,179 x 106). Other parameters, including date of PolyTreg production, patient sex, and patient age did not significantly correlate with fold expansion of Treg during product manufacturing. The main correlate of post-expansion cell number was starting cell number, which positively correlates with absolute circulating Treg cell count. In conclusion, PolyTreg manufacturing outcomes are consistent across trials and dates of production.